Substrate-controlled Rh(iii)-catalyzed regiodivergent annulation towards fused and spiro benzimidazoles. Issue 34 (16th August 2022) - Huang, Ying-Ti; Barve, Indrajeet J.; Huang, Yi-Ting; Dhole, Sandip; Chiu, Wei-Jung; Sun, Chung-Ming
Abstract : Switchable selectivity towards the formation of two distinct products, benzimidazole-fused isoquinolines and benzimidazole-spiro isoindoles, can be achieved using unsubstituted and substituted benzimidazoles at the ortho -position of the phenyl ring. Abstract : A Rh(iii )-catalyzed cascade C–H activation and cyclization of 2-aryl benzimidazoles with maleimides for the synthesis of benzimidazole-fused isoquinolines and benzimidazole-spiro isoindoles is reported. Switchable selectivity towards the formation of these two distinct products can be achieved using unsubstituted and substituted benzimidazoles at the ortho -position of the phenyl ring. Mechanistically, C–H activation followed by migratory insertion of maleimide forms a Heck-type intermediate. Unsubstituted benzimidazole undergoes aza-Michael addition to form a (4 + 2) fused product, whereas ortho -substituted phenyl benzimidazole causes steric clash to deliver a (4 + 1) spiro-adduct favorably via acid-catalyzed intramolecular annulation.